ArfGAP1 restricts Mycobacterium tuberculosis entry by controlling the actin cytoskeleton. (15th November 2017) - Song, Ok‐Ryul; Queval, Christophe J; Iantomasi, Raffaella; Delorme, Vincent; Marion, Sabrina; Veyron‐Churlet, Romain; Werkmeister, Elisabeth; Popoff, Michka; Ricard, Isabelle; Jouny, Samuel; Deboosere, Nathalie; Lafont, Frank; et al.
Abstract: The interaction of Mycobacterium tuberculosis (Mtb) with pulmonary epithelial cells is critical for early stages of bacillus colonization and during the progression of tuberculosis. Entry of Mtb into epithelial cells has been shown to depend on F‐actin polymerization, though the molecular mechanisms are still unclear. Here, we demonstrate that mycobacterial uptake into epithelial cells requires rearrangements of the actin cytoskeleton, which are regulated by ADP‐ribosylation factor 1 (Arf1) and phospholipase D1 (PLD1), and is dependent on the M3 muscarinic receptor (M3 R). We show that this pathway is controlled by Arf GTPase‐activating protein 1 (ArfGAP1), as its silencing has an impact on actin cytoskeleton reorganization leading to uncontrolled uptake and replication of Mtb. Furthermore, we provide evidence that this pathway is critical for mycobacterial entry, while the cellular infection with other pathogens, such as Shigella flexneri and Yersinia pseudotuberculosis, is not affected. Altogether, these results reveal how cortical actin plays the role of a barrier to prevent mycobacterial entry into epithelial cells and indicate a novel role for ArfGAP1 as a restriction factor of host–pathogen interactions. Synopsis: Mycobacterial uptake into epithelial cell is dependent on the receptor M3R and requires actin rearrangements regulated by Arf1. This pathway is controlled by ArfGAP1, demonstrating its role in the regulation of host‐pathogen interactions. Colonization by M. tuberculosis depends on the M3 muscarinic receptor (M3R) and the activation of Arf1 and PLD1. M3R‐mediated entry of M. tuberculosis into epithelial cells is restricted by the Arf GTPase‐activating protein ArfGAP1. Mycobacterial entry involves rearrangements of the actin cytoskeleton controlled by ArfGAP1. Abstract : Mycobacterial uptake into epithelial cell is dependent on the receptor M3R and requires actin rearrangements regulated by Arf1. This pathway is controlled by ArfGAP1, demonstrating its role in the regulation of host‐pathogen interactions.